Go for it: Where IS researchers aren’t researching - Saunders, Carol; Rutkowski, Anne-F. (International Journal of Information Systems and Project Management, 2021)
This viewpoint article describes two research topics under-researched by Information Systems (IS) researchers: Robotics and IT addiction. These topics offer great potential for IS researchers in terms of business and societal impacts and it would behoove IS researchers to study them more fully. The aspects of the research topics that are related to IS are discussed and potential research areas and questions are suggested.